Accuracy of Laboratory Data Communication on ICU Daily Rounds Using an Electronic Health Record - Artis, Kathryn A; Dyer, Edward; Mohan, Vishnu; Gold, Jeffrey A (Critical care medicine, 2017)
Accurately communicating patient data during daily ICU rounds is critically important since data provide the basis for clinical decision making. Despite its importance, high fidelity data communication during interprofessional ICU rounds is assumed, yet unproven. We created a robust but simple methodology to measure the prevalence of inaccurately communicated (misrepresented) data and to characterize data communication failures by type. We also assessed how commonly the rounding team detected data misrepresentation and whether data communication was impacted by environmental, human, and workflow factors. Direct observation of verbalized laboratory data during daily ICU rounds compared with data within the electronic health record and on presenters' paper prerounding notes. Twenty-six-bed academic medical ICU with a well-established electronic health record. ICU rounds presenter (medical student or resident physician), interprofessional rounding team. None. During 301 observed patient presentations including 4,945 audited laboratory results, presenters used a paper prerounding tool for 94.3% of presentations but tools contained only 78% of available electronic health record laboratory data. Ninty-six percent of patient presentations included at least one laboratory misrepresentation (mean, 6.3 per patient) and 38.9% of all audited laboratory data were inaccurately communicated. Most misrepresentation events were omissions. Only 7.8% of all laboratory misrepresentations were detected. Despite a structured interprofessional rounding script and a well-established electronic health record, clinician laboratory data retrieval and communication during ICU rounds at our institution was poor, prone to omissions and inaccuracies, yet largely unrecognized by the rounding team. This highlights an important patient safety issue that is likely widely prevalent, yet underrecognized.